Transformasi Akad Muamalah Klasik dalam Produk Perbankan Syariah - Jamal Abdul Aziz (IAIN Ponorogo, 2012)
Basically islamic banking products derived from classical mu ’amalah contracts as explained in many various books of Islamic law(kutub al-fiqh). Since such the contracts are not applicable in banking system, it is required many efforts to transform them into banking system. There were two forms of contract transformation, firstly modification of classical mu ’amalah contracts in limit sense. In this modus, they were modified to be applicable in banking context. These forms can be reflected at the applications of muda>rabah, musya>rakah, and mura>bahah in Syari ’ah banking. Secondly, creating new contracts derived from the classical m ’uamalah contracts, for examples the contract of musya>rakah mutana>qisah and al-ija>rah al-muntahiyah bi al-tamli>k. Both contracts have never been known in classical mu ’amalah contracts. In the opinion of some muslim scholars, some modified contracts in shari’ah banking are not appropriate the rules of mu ’amalah shar ’iyah, among them are the applications of mura>bahah, muda>rabah, and musya>rakah. The application of murabahah contract, for example, deemed the same as the loan with fixed rate of interest.